A Pragmatic Analysis Of Compliment Utterances And Its Response In The Romantic Movies Manuscript - Widyaningrum, Ayu Fitriana; , Agus Wijayanto, Ph. D.; , Drs. Sigit Haryanto, M.Hum (2013)
This research aimed to describe the variations of the compliment topics used by the characters, to classify the variations of compliment responses between male and female, and to identify the differences of politeness strategies used by male and female in expressing compliment response in the romantic movies manuscript. The study used descriptive qualitative research. The data were utterances that contained compliment utterances and responses. The data source is the data in The Romantic movies manuscript, especially Pride and Prejudice and Shakespeare in Love movies. The data were collected by documentation, then the data were classified, analyzed, and drawn the conclusion. The research findings showed the compliment topic between male to male tended to use a compliment about possession (37.5%). For male to female tended to give a compliment about physical appearance (37.5%). Female to female tended to give a compliment about PA and ability (44.44%). For female to male tended to give a compliment about physical appearance (42.86%). As for compliment response, there was also a different response between the gender of addressee and addresser. Male tended to use praise upgrade and no acknowledgment type (20%) to male. Male tended to use appreciation token type to female (27.27%). Then, female tended to use reassignment type (27.27%) to female, but female tended to use no acknowledgment type (26.67%) to male. As for politeness used by male to male of those movies had tendency to use positive politeness (38.46%) and bald on record (30.77%). As for politeness used by male to female had tendency to use positive politeness (55.56%). Next, as for politeness strategy used by female to female had tendency to use positive politeness (44.44%). As for politeness strategy used by female to male had tendency to use positive politeness (58.33%).